Effect of Fe substitution on the cation distribution and magnetic properties of CoCr2-xFexO4 (x = 0.6 to 1.0) nanoparticles - Kumar D.; Pandey G.C.; Banerjee A.; Mahmoud A.; Rath C. (My University, 2025)
Evolution of the structure, microstructure, cation distribution, and magnetic properties of CoCr2-xFexO4 nanoparticles with increase in x from 0.6 to 1.0 synthesized through a coprecipitation technique is demonstrated. While X-ray diffraction shows a cubic phase with space group Fd3‾m, the cation distribution qualitatively examined by extended X-ray absorption fine structure is further quantified by Mössbauer spectroscopic measurements. We reveal that although Cr3+ ions have a strong preference for the B site, Fe3+ and Co2+ ions are found to be distributed among A and B sites. As a consequence, the normal spinel CoCr2O4 transforms to a mixed spinel type showing a decrease in the degree of inversion of Fe ions from 30% to 7% at the tetrahedral (A) site with increase in x from 0.6 to 1.0, whereas Fe3+ ions are found to be equally distributed among A and B sites for x = 0.3. The paramagnetic to ferrimagnetic transition temperature, TC, is increased from 263 K for x = 0.6 to above room temperature for x = 1.0 compared with 97 K obtained for x = 0. The maximum magnetization calculated from the M-H curve increases from 0.18 μB per formula unit for x = 0–0.32 μB per formula unit for x = 0.6 and reaches 3.71 μB per formula unit for x = 1.0. The frequency-dependent ac susceptibility confirms spin glass behavior irrespective of the composition, including x = 0. © 2020 Elsevier Ltd